2022
DOI: 10.3390/jpm12060987
|View full text |Cite
|
Sign up to set email alerts
|

The Greek Collaborative Long COVID Study: Non-Hospitalized and Hospitalized Patients Share Similar Symptom Patterns

Abstract: Long COVID-19 syndrome refers to persisting symptoms (>12 weeks) after the initial coronavirus infection and is estimated to affect 3% to 12% of people diagnosed with the disease globally. Aim: We conducted a collaborative study with the Long COVID patient organization in Greece, in order to estimate the characteristics, symptoms, and challenges these patients confront. Methods: Data were collected from 208 patients using unstructured qualitative free-text entries in an anonymized online questionnaire. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Katsarou et al ( 2022 ) developed a 14-item online questionnaire for their cross-sectional study, in which one of the items assessed the presence of parosmia: “Long COVID symptoms (please use a comma to separate each symptom).” Researchers analyzed the results by identifying term frequencies, of which parosmia was regarded as one of the categories. The question itself, however, allows for general and specific symptoms that participants themselves have to provide and define.…”
Section: Resultsmentioning
confidence: 99%
“…Katsarou et al ( 2022 ) developed a 14-item online questionnaire for their cross-sectional study, in which one of the items assessed the presence of parosmia: “Long COVID symptoms (please use a comma to separate each symptom).” Researchers analyzed the results by identifying term frequencies, of which parosmia was regarded as one of the categories. The question itself, however, allows for general and specific symptoms that participants themselves have to provide and define.…”
Section: Resultsmentioning
confidence: 99%
“…A study done by COMEBAC study group 14 found out that 51% had at least 1 new A study done by Anushri, et al 15 found that pulmonary, neuropsychiatric and cardiovascular symptoms were more predominant same as our findings. The Greek Collaborative Long Covid Study 16 found out that patients who had mild symptoms during COVID 19 infection suffer from same persistent symptoms as patients who were hospitalized. In our study we included both hospitalized and out patients too, although they were predominantly outpatients.…”
Section: Resultsmentioning
confidence: 99%
“…Recent rehabilitation frameworks highlight the need for rehabilitation experts to mitigate both direct and indirect impacts of COVID-19, and to help older adults be as physically active and mobile as possible to counteract both the effects of lockdown and to promote recovery from illness. 6,42 Our study is the first, to our knowledge, to examine the factors associated with mobility using a validated and standardized self-report measure during the pandemic. Other comparable research used non-validated measures, 36 or life space mobility assesments, 34,43,44 which makes interpretation challenging since changes in life space mobility may be due to public health restrictions rather than declines in older adults' capabilities.…”
Section: Discussionmentioning
confidence: 96%